Avaliação do potencial de extratos ricos em flavonoides de Kalanchoe laciniata (L.) DC e Bryophyllum pinnatum (Lam.) Oken no tratamento de doença inflamatória intestinal: um estudo fitoquímico, de segurança e eficácia em modelos in vivo - Andrade, Anderson Wilbur Lopes (2021)
Inflammatory bowel disease (IBD) such as ulcerative colitis and Crohn’s disease are characterized by chronic inflammation in the intestine. Currently, there are several therapeutic strategies to treating IBD. However, some treatments of choice are associated with serious adverse effects, which justifies the search for new adjuvant treatments. In this sense, the interest in plants rich in phenolic compounds with immunomodulatory and antioxidant properties stands out, such as Kalanchoe laciniata and Bryophyllum pinnatum, belonging to the Crassulaceae family. These plants are popularly used in Brazil to treat gastritis, ulcer, inflammation in general, among others. Thus, our hypothesis was evaluate if K. laciniata (HEKL) and B. pinnatum (HEBP) hydroethanolic leaf extracts 50 % demonstrate signs of cytotoxicity (RAW 264.7 cells) and acute (14 days) and subchronic (28 days) toxicity in vivo models and intestinal anti-inflammatory effect in two colitis models: induction by 2.4-dinitrobenzene sulfonic acid (DNBS) in rats (preventive protocol) and by dextran sulfate sodium (DSS) in mice (curative protocol). Initially, the total content of phenols and flavonoids in the extracts was performed. HEKL and HEBP demonstrated, respectively, contents of 75.1±6.32 and 96.7±7.34 mg (gallic acid/g of the extract) and total flavonoids equal to 37,4±4.82 and 64.3±4.16 mg (quercetin/g of the extract). Ultra-fast liquid chromatography methods to evaluate the major constituents of the two extracts was developed and validated. However, only the method for HEBP has been validated according to the Brazilian legislation and its major flavonoids quercetin 3-O-α-Larabinopyranosyl-(1→2)-α-L-rhamnopyranoside, kaempferol 3-O-α-L-arabinopyranosyl- (1→2)-α-L-rhamnopyranoside and quercetin-3-O-rhamnopyranoside had, respectively, contents of 35.56±0.09, 4.66±0.08 and 4.56±0.03 mg per g of extract. The HEKL and HEBP did not show signs of cytotoxicity and in the toxicological assay, the tested extracts did not significantly alter (p <0.05) the control parameters (behavioral, locomotor, hematological, biochemical, among others) and did not cause death in the animals (median lethal dose estimated above 2000 mg/kg). Regarding the anti-colitic effect in the DNBS and DSS models, it was observed that the extracts have chemopreventive and anti-inflammatory effects by reducing the disease activity index score (p < 0.05) and macroscopic and microscopic. The extracts promoted negative regulation (p < 0.05) of the Toll-type receptor and the expression of the nuclear factor kappa B p65 gene, causing a suppression (p < 0.05) of the proinflammatory mediators (necrosis factor tumoral alpha and interleukins (IL) 1β, IL-6, IL-17) and oxidants (nitric oxide), chemokines (monocyte chemoattractant protein-1 and macrophage inflammatory protein-2), type I intercellular adhesion molecules. This immunomodulatory and antioxidant properties were proposed as one of the mechanisms of action of the extracts. The improvement in intestinal inflammation was also associated with a decrease in oxidative stress and leukocyte infiltration exerted by the extracts. In addition, HEKL and HEBP contributed to maintaining the integrity of the intestinal epithelial barrier by restoring the expression of proteins (p < 0.05) associated with mucosal protection (mucin (MUC) 2 and MUC-3, occludin, zonula occludens type 1, trefoil factor, villin). Based on the finding that the extracts did not present toxic effects in the tested doses, and the beneficial effects in the DNBS and DSS models, it can be inferred that HEKL and HEBP are safe and that they have an anti-inflammatory effect compared to the models applied that can be hypothesized by antioxidant and immunomodulatory properties of its flavonoids. These findings make the extracts as a promising candidate for assessing the efficacy and clinical safety of adjuvant therapy for IBD.